Permen Jelly Andaliman: Pembuatan dan Inovasi Lezat untuk Menangkal Hipertensi - Panduwati, Digna Renny (Borneo Community Health Service Journal, 2024)
Hypertension is a condition where there is a chronic increase in blood pressure (over a long period) which can cause pain to a person and can even cause death. Andaliman as a source of biodiversity contains flavonoids, especially the compound quercetin which has ACE-I activity 30% so it has the potential to be a natural antihypertensive. This method of implementing community service begins with giving a pre-test regarding hypertension to see the respondent's initial knowledge and continues with socialization regarding hypertension. The activity was continued with training how to make andaliman jelly candy. The activity was closed by providing a post-test and health examination in the form of measuring blood pressure, blood sugar levels, cholesterole and uric acid. The results is PKK mothers became more aware of the food they consumed and which could cause hypertension. PKK women have additional knowledge regarding the processing of andaliman apart from being a spice. The creativity of PKK mothers also increases by knowing how to package attractive andaliman jelly candy. Based on the results of health examinations, it is known that there are still many PKK mothers who have high blood pressure accompanied by high cholesterol